Prevalence of acute respiratory infections among under five children in a rural area of Kozhikode district, Kerala - Vijayan, Binsu; L., Dhilmon T.; Johnson, Liaquat Roopesh (International Journal Of Community Medicine And Public Health, 2019)
Background: Although childhood acute respiratory infections (ARI) is a significant public health problem in India, robust epidemiological data on its prevalence is not available. This study was done to estimate the prevalence of ARI in under five children and study the factors responsible for the same in a rural area of Kozhikode District. Methods: This cross sectional study was conducted in 386 under-5 children in Kunnamangalam panchayat of Kozhikode district from June 2015 to June 2016. Employing cluster sampling technique, data regarding socio demographic factors, prevalence of ARI and selected factors were collected using a pre tested semi structured questionnaire. Results: The overall prevalence of ARI in children was 31.9 %. Prevalence was slightly higher in boys (32.7%) than in girls (31.1%). The prevalence of ARI was more in lower social class children (36.1%), compared to those from upper social class (26.3%). ARI was higher in children living in overcrowded houses (40.2%), poorly ventilated houses (37.8%), houses in which there were no smoke outlets (43.1%), houses having pets (58.6%). Underweight children were also found to have higher rates of ARI (46.5%). Binary logistic regression revealed that after adjusting for all other factors, age less than 1 year (OR 0.48, p=0.02) and nuclear family (OR 0.10, p=0.01) are significant independent protective factors for ARI. Conclusions: Among under-5 children, younger age and membership in a nuclear family are significant protective factors for ARI.